2023
DOI: 10.1007/s13132-023-01116-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of High-tech Exports: New Evidence from OECD Countries

Abstract: High export capacity is a key element for sustained long-term economic growth. To achieve this goal, the technological sophistication of exports plays a key role. To enhance exports with a high level of technological sophistication, it is critical to target key drivers of high-tech exports. Hence, this article studies the determinants of international trade flows of manufactures according to their technological content in the case of OECD countries. Given a panel of 35 countries and 15 years (2004 to 2018), pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Palestine has not undergone a significant technological upgrade in its exports. Therefore, it is crucial to target key drivers of hightech exports to enhance the level of technological sophistication in exports (Zapata et al, 2023). In analyzing the drivers of technology-intensive exports, research studies have identified variables that play a role in the technological level of countries' export.…”
Section: Table 5 Hypothesis' Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Palestine has not undergone a significant technological upgrade in its exports. Therefore, it is crucial to target key drivers of hightech exports to enhance the level of technological sophistication in exports (Zapata et al, 2023). In analyzing the drivers of technology-intensive exports, research studies have identified variables that play a role in the technological level of countries' export.…”
Section: Table 5 Hypothesis' Resultsmentioning
confidence: 99%
“…In analyzing the drivers of technology-intensive exports, research studies have identified variables that play a role in the technological level of countries' export. These variables include research & development expenditures, the quality of human capital, foreign direct investment, technological specialization, level of economic freedom, and countries' openness to international trade (Zapata et al, 2023). To improve high-tech exports in Palestine, enhancing policies and investments targeted towards the technology and innovation sector can drive economic development.…”
Section: Table 5 Hypothesis' Resultsmentioning
confidence: 99%
“…This approach has unique advantages as it can more specifically reveal how technological innovation directly affects the competitive positioning of individual products [23]. The export competitiveness of high-tech products is an important component of national competitiveness [24], influenced by a variety of factors including research and development investments [25,26], human capital [27], and government policies [28].…”
Section: Introductionmentioning
confidence: 99%